A questão do negro e políticas públicas de educação multicultural: avanços e limitações - Gonçalves, Luciane Ribeiro Dias (2004)
Through 90 years, in lhe brazilian educacional context, various Public policies which intend lhe racial question inclusion in the emerging discussions. The goal oflhis dissertation is to aualyse the normative-juridical framework produced in thatdeeade and so how itinfluences in the scholar eurriculum as to investigale how ofTicial porpuscs are being put down and brought arised in the scholar daily, in orderto evidence its advancements and limilations. The qualificativo inquiry scrutinizes two (ields about the subjeeL. The former examines the set ofdocuments related to the multicultural potenciality ofcurl and edueational legislation. Federal Constitution fron 1988, Bases and Directrixcs Law (Law n° 9394/96), Nacional Curricular Parameters, mainly the Cultural Divcrsity aspect, and Law 10639/03 are analysed either lheir legal impacts. The focus is based on lhe way these legal condilious point to multicultural practices, principally the ones closest to Negro culture. The second lield scarches the consequences ofthose Public Policies when theycome to scholar context and how thcy coopcrate in elaborating a less hegemonia and eurocentrie eurriculum which determines the public schools routine. Based on thosc goals, the data was provided by semi-slruetured interviews. The analyses are supported by criticai multiculturalism that established changes in the scholar context and in the society in order to bccome them jouster. Brazilian-afro culture was inclused in the scholar eurriculum by various legal dispositions are ineíTicacious in pursuing antiexcluded actions to respcct Public Policies either to scholar routine.